Evaluación de la ejecución presupuestal del programa 131: control y prevención en salud mental de la Dirección Regional de Salud Loreto, periodo 2018 - 2019 - Muñoz Martinez, Abril Antuanet (2021)
The main objective of this research is to evaluate the budget execution of the program 131 control and prevention in mental health of the Regional Directorate of Health Loreto, period 2018 - 2019. The research has as a non-experimental research design, of a simple descriptive type, analyzing the income and expenses of the budget program 131: control and prevention in mental health of the Loreto Health Directorate, period 2018-2019, analyzing the execution by type of expenditure: Current expenses, capital expenses, debt service, among others. It was concluded that the budget execution of program 131: control and prevention in mental health of the Loreto Regional Health Directorate, period 2018 - 2019, reached S /. 6,737,237.00; equivalent to 98.28% of income, this concept is made up of current expenses and capital expenses. The analysis of the income of program 131: control and prevention in mental health of the Loreto Regional Health Directorate, period 2018 - 2019, shows that they were mainly determined by the “Ordinary Resources” that amounted to the sum of S/.5,811,166.00 equivalent to 84.77% of total income.